Identifikasi Potensi Pemberdayaan Harta Zakat Wilayah Perbatasan Melalui Pendekatan Analisis Wacana Kritis (Kecamatan Sebatik Tengah, Provinsi Kalimantan Utara) - Fadly Yashari Soumena (Program Studi Ekonomi Syariah, 2019)
Zakat is one of the fundamental instruments in Islam which has economic functions to improve the economic welfare of the poor. Social issues in Indonesia can be seen in the problems of border areas, such as Sebatik Island, Nunukan Regency, North Kalimantan Province. The purpose of this study is to explain the potential implementation of zakat empowerment in the region, especially in one of the sub-districts on Sebatik Island, Central Sebatik. The method used in this study is Norman Fairclough's Critical Discourse Analysis. The results showed that there were two main potentials that could be developed and empowered with zakat in Central Sebatik Sub-districts. These potentials are plantations (nature) and human quality (education). Empowerment of zakat is also in the form of business capital assistance with Qardhul Hasan contract, educational scholarship, and management of religious education institutions. These three concepts will produce an zakat ecosystem by using territories such as zakat villages.